The Unifying Hypothesis of Alzheimer’s Disease: Heparan Sulfate Proteoglycans/Glycosaminoglycans Are Key as First Hypothesized Over 30 Years Ago - Snow, Alan David; Cummings, Joel A.; Lake, Thomas (Frontiers in Aging Neuroscience, 2021)
The updated “Unifying Hypothesis of Alzheimer’s disease” (AD) is described that links all the observed neuropathology in AD brain (i.e., plaques, tangles, and cerebrovascular amyloid deposits), as well as inflammation, genetic factors (involving ApoE), “AD-in-a-Dish” studies, beta-amyloid protein (Aβ) as a microbial peptide; and theories that bacteria, gut microflora, gingivitis and viruses all play a role in the cause of AD. The common link is the early accumulation of heparan sulfate proteoglycans (HSPGs) and heparan sulfate glycosaminoglycans (GAGs). HS GAG accumulation and/or decreased HS GAG degradation is postulated to be the key initiating event. HS GAGs and highly sulfated macromolecules induce Aβ 1–40 (but not 1–42) to form spherical congophilic maltese-cross star-like amyloid core deposits identical to those in the AD brain. Heparin/HS also induces tau protein to form paired helical filaments (PHFs). Increased sulfation and/or decreased degradation of HSPGs and HS GAGs that occur due to brain aging leads to the formation of plaques and tangles in AD brain. Knockout of HS genes markedly reduce the accumulation of Aβ fibrils in the brain demonstrating that HS GAGs are key. Bacteria and viruses all use cell surface HS GAGs for entry into cells, including SARS-CoV-2. Bacteria and viruses cause HS GAGs to rapidly increase to cause near-immediate aggregation of Aβ fibrils. “AD-in-a-dish” studies use “Matrigel” as the underlying scaffold that spontaneously causes plaque, and then tangle formation in a dish. Matrigel mostly contains large amounts of perlecan, the same specific HSPG implicated in AD and amyloid disorders. Mucopolysaccharidoses caused by lack of specific HS GAG enzymes lead to massive accumulation of HS in lysosomal compartments in neurons and contribute to cognitive impairment in children. Neurons full of HS demonstrate marked accumulation and fibrillization of Aβ, tau, α-synuclein, and prion protein (PrP) in mucopolysaccharidosis animal models demonstrating that HS GAG accumulation is a precursor to Aβ accumulation in neurons. Brain aging leads to changes in HSPGs, including newly identified splice variants leading to increased HS GAG sulfation in the AD brain. All of these events lead to the new “Unifying Hypothesis of Alzheimer’s disease” that further implicates HSPGs /HS GAGs as key (as first hypothesized by Snow and Wight in 1989).